In vitro bioaccessibility and bioavailability of iron from potatoes with varying Vitamin C, carotenoid, and phenolic concentrations - André, C.M.; Evers, D.; Ziebel, J.; Guignard, C.; Hausman, J.F.; Bonierbale, Merideth W.; Felde, T. zum; Burgos, G. (American Chemical Society, 2015)
The purpose of this study was to compare the in vitro iron availability from diverse iron biofortified International Potato Center (CIP) potato clones grown in the Peruvian Andes and, thereby, to provide key information to breeders seeking to increase bioavailable iron from potato.